2016
DOI: 10.1093/ndt/gfw254
|View full text |Cite
|
Sign up to set email alerts
|

Serum sodium and mortality in a national peritoneal dialysis cohort

Abstract: A B S T R A C TBackground: Sodium disarrays are common in peritoneal dialysis (PD) patients, and may be associated with adverse outcomes in this population. However, few studies of limited sample size have examined the association of serum sodium with mortality in PD patients, with inconsistent results. We hypothesized that both hypo-and hypernatremia are associated with higher death risk in a nationally representative cohort of US PD patients. Methods: We sought to examine the association of serum sodium over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 44 publications
3
42
2
4
Order By: Relevance
“…Dysnatremia in CKD and ESRD has mortality significance. A U-shaped association between serum Na and mortality was found in both non-dialysis CKD [123,127] and dialysis patients [128,129]. The management of dysnatremia in CKD patients is similar to that for the general patients and should start with identifying and, if possible, correcting the underlying cause.…”
Section: Other Electrolyte Derangementsmentioning
confidence: 99%
“…Dysnatremia in CKD and ESRD has mortality significance. A U-shaped association between serum Na and mortality was found in both non-dialysis CKD [123,127] and dialysis patients [128,129]. The management of dysnatremia in CKD patients is similar to that for the general patients and should start with identifying and, if possible, correcting the underlying cause.…”
Section: Other Electrolyte Derangementsmentioning
confidence: 99%
“…These include changes of urine dilution and concentration in response to antidiuretic hormone, and alteration of water and Na and CI reabsorption and excretion 13,14 . Previous studies have reported that dysnatremias and hypochloremia are associated factors for mortality in patients with chronic kidney disease (CKD), with or without dialysis [15][16][17][18][19][20][21][22] . Thus, dyschloremias and dysnatremias have been proposed as potential useful factors for mortality prediction in this population [15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Most mortality studies in hyponatraemia have been retrospective, and as a result, there has been poor ascertainment of the essential diagnostic criteria of SIAD. [2][3][4][5][6][7][8][9][10][11][12][18][19][20] On the basis of existing data; therefore, it is not possible to distinguish between the mortality in SIAD, and that associated with hypovolaemic hyponatraemia (HON) or hypervolaemic hyponatraemia (HEN). [2][3][4][5][6][7][8][9][10][11][12]14,15 The aim of this study was to clearly define the mortality in SIAD, with specific reference to the following questions; (i) whether mortality in a well-defined cohort of SIAD patients was elevated compared to eunatraemic controls, (ii) whether the increased mortality was explainable on the basis of comorbid conditions and (iii) whether the mortality in SIAD was different to that in patients with HON or HEN.…”
Section: Introductionmentioning
confidence: 99%